PENYULUHAN HUKUM SURAT IZIN PERIKANAN DI DESA CIKONENG KABUPATEN SERANG - Anom, Surya; Jumena, Mas Nana (Jurnal Pengabdian Dinamika, 2017)
As the fishermen must have permissions when they are going to do the fishing in the sea. Permission is a thing that must be owned by the fishermen so that they are not categorized as the theft of fish (illegal fishing) so that they may incur sanctions based on the applicable law.Based on the condition, need to be pursued and extension activities of the law to the fishermen community so that they can manage the marine resources, particularly fish resource with responsible and sustainable or at least fishing activities that they did not illegal.Coastal Community development is an integral part of the management of coastal and marine resources for the prosperity of society that it needs to be used an approach where the community as an object as well as the subject of development.Coastal Community Development Strategy, is seen not only as social and cultural issues but more as an integral part of the problem, therefore, resolution need to be done through a comprehensive strategy by placing the social-economic system and cultural values that are inherent in the community as a factor driving the changes.